Сравнительный анализ переменного магнитного поля на поверхности ротора турбогенераторов с разным числом зубцов статора в режиме нагрузки - Милых, Владимир Иванович; Полякова, Наталия Владимировна (Інститут електродинаміки НАН України, 2014)
Представлен метод расчета переменного магнитного поля на поверхности ротора синхронных машин. Он основан на многопозиционных численно-полевых расчетах магнитного поля при вращении ротора и изменении токов в обмотке статора. При этом учитываются реальная геометрия электромагнитной системы и насыщение магнитопровода. Выполнены сравнительный расчет и гармонический анализ переменной составляющей магнитной индукции в режиме номинальной нагрузки для двух турбогенераторов с разным числом зубцов сердечника статора. Предложенный метод универсален для разных электрических машин и режимов их возбуждения.

The method of calculating of the variable magnetic field is presented on the rotor surface of the synchronous machines. It is based on the multi-position numerical field calculations of the magnetic field in rotating of the rotor and the changing currents in the stator winding. This takes into account the real geometry of the electromagnetic system and the saturation of the magnetic core. A comparative calculation and harmonic analysis of the variable component of the magnetic induction are performed in the mode of the rated load for the two turbogenerators with a different amounts of teeth of the stator core. The proposed method is universal for different electric machines and modes of their excitation.
Comparative analysis of the variable magnetic field on the surface of the rotor of turbogenerators with different numbers of stator teeth in the load condition
Keywords: индукция магнитная; метод численно-полевой; расчет; анализ гармонический; turbogenerator; rotor surface; variable component; magnetic induction; numerical field calculation; comparative calculation; stator teeth; harmonic analysis; load condition mode